KETERLIBATAN ORANG TUA DALAM PENANGANAN ANAK BERKEBUTUHAN KHUSUS (DISABLITAS SOSIAL) - Elisabeth F Lekatompessy; Janne E Kumbubui; Yemima Rumahpasal; Melsiana Tasidjawa; Robi lehalima (Nusantara Hasana Journal, 2026)
Parental involvement constitutes a crucial factor in the care and development of children with special needs (CSN). Empirical studies demonstrate that parental support and active participation exert a significant impact on the social, emotional, and academic development of children with disabilities. This study aims to analyze the importance of parental involvement in the management of children with special needs and to identify the factors influencing the effectiveness of such involvement based on recent scholarly literature. This research employs a systematic literature review method of studies published between 2020 and 2025 addressing parental involvement in the care and intervention of children with special needs. The findings indicate that optimal parental involvement encompasses several key dimensions, including acceptance of the child’s condition, effective communication with professionals, participation in therapeutic programs, and the provision of structured support within the home environment. The factors influencing the effectiveness of parental involvement include parents’ educational level, socioeconomic status, access to services, and the availability of social support. It can therefore be concluded that active and structured parental involvement significantly enhances developmental outcomes for children with special needs. Consequently, systematic training programs and sustained support mechanisms for parents of children with special needs are strongly recommended.